PERUBAHAN KADAR AIR DAN ASAM LEMAK BEBAS PADA TAHAP KLARIFIKASI MINYAK SAWIT - Riski Darma; Novriaman Pakpahan (Faculty of Agriculture Science & Technology, 2022)
Common indicators used to evaluate the quality of crude palm oil are moisture and free fatty acids content. This study was aimed to find the changes in water content and free fatty acids at the clarification stage and evaluate the processing of crude palm oil at PT Socfin Indonesia Seunagan Estate. The study was conducted by taking samples at several processing station end points, including vibrating screen, continuous settling tank, oil tank and vacuum dryer. Furthermore, samples were also taken from the oil tank and vacuum dyer with different time periods (1 hour, 2 hours, 3 hours and 4 hours). The results showed that crude palm oil at the final stage of clarification had water and free fatty acid content of 0.12% and 2.25%. This value met the quality standards of PT Socfindo and SNI. The moisture content decreased exponentially during the processing process in the oil tank and vacuum dryer. The decrease in water content followed the function y = 0.3519x-0.213 in the oil tank and y = 0.253x-0.532 in the vaccum. Furthermore, the decrease in free fatty acids also occurred exponentially in the vacuum dryer with a function of y = 2.3355x-0.03. This functional equation can be used to predict the processing time required for oil tanks and vacuum dryers to remove water and free fatty acids.